Unveiling Complex Dynamics Shaping the Experiences of Trainees in Entry-Level Roles : The Hexagon of Trainee Success - Sand, Anna (My University, 2023)
Trainee programs play a significant role in the professional development of young professionals. These programs and their implications have been thoroughly explored in academia and researched from an organizational perspective. This thesis provides a new angle by contributing the experiences of trainees. Despite existing research, the impact of methods used, experiences, and social environment on trainees remains an unexplored gap in the academic field. The study was conducted by creating a theoretical framework covering organizational culture, integration into the organization, and interrelations and commitments in the work environment. This was achieved by integrating theories such as organizational culture theory, job embeddedness theory, social exchange theory, and psychological contract theory. Applying these theories to the context of trainees, and combining them with narratives collected via interviews, provided a clear trainee perspective. The results indicate that the theoretical framework applies to trainees. However, trainees have significantly less power than organizations, resulting in a power imbalance favoring organizations in trainee programs. The study identified six elements that support a positive trainee experience. The Hexagon of Trainee Success framework illustrates these elements, enhancing learning outcomes and increasing motivation during trainee programs. This research revealed that in the post-COVID-19 world, many organizations have not fully adapted to the new requirements of organizing trainee programs. Trainees often require different forms of support and working styles compared to more senior employees. Additionally, many trainees are left with programs that are inadequately designed, organized, or led. As organizations hold more power in this relationship, trainees end up leaving due to unmet needs. Ultimately, every organization should critically assess its trainee programs, striving to meet trainees' needs, leading to longer employments, improved performance, and increased employer satisfaction.
Keywords: trainee, trainee program, trainee experience